Implementasi Model Pembelajaran Numbered Heads Together Berbasis Alat Peraga Pada Materi Lingkaran Ditinjau Dari Komunikasi Matematika Siswa Kelas VIII SMP Muhammadiyah 1 Kartasura - Izza, Uliya Fathul; , Dra. Nining Setyaningsih,M.Si (2017)
This study aimed to analyze and examine: (1) a significant influence of the application of learning model Numbered Head Together based teaching aids to the mathematics learning outcomes, (2) a significant influence of mathematics communication on the mathematics learning outcomes, (3) the interaction between the learning model Numbered Heads Together based teaching aids and communication of mathematics on mathematics learning outcomes. This type of research is based on a quantitative approach to research design using a quasi-experimental design. The population in this study were students of class VIII B, VIII C, and VIII D SMP Muhammadiyah 1 Kartasura Year 2016/2017. The sampling technique used in this study is a random cluster sampling technique. Data collection techniques in this study is a questionnaire, test methods, and methods of documentation. Data analysis techniques used in this study is a two-way analysis of variance with different cells. With a significance level of 5% was concluded that: (1) There is a significant influencet of the application of the learning model Numbered Heads Together based teaching aids to the mathematics learning outcomes by FA = 146.058. (2) There is a significant influence of mathematics communication on mathematics learning outcomes with FB = 47.339. (3) There is no interaction between the learning model and communication of mathematics on mathematics learning outcomes with FAB = 1.557.